Impact Of A Transfer Of Knowledge And Skill Based Intervention On Caregivers’ Knowledge, Attitudes, And Practices In Badung Regency - Ni Nengah Ariati; Ga Dewi Kusumayanti; Ia Eka Padmiari (CV. AFDIFAL MAJU BERKAH, 2026)
Early childhood is a critical period characterized by rapid growth and development, requiring adequate nutritional intake and appropriate caregiving practices. This study aimed to examine the effectiveness of the Transfer of Knowledge and Skill (TKS) model in improving caregivers’ knowledge, attitudes, and childcare practices related to nutrition. A quasi-experimental study was conducted from July to October 2025 in Canggu Village (North Kuta District) and Pererenan Village (Mengwi District). A total of 58 caregivers were divided into a control group receiving conventional caregiving and an intervention group receiving the Transfer of Knowledge and Skill model. Data were analyzed using independent samples t-tests for homogeneous data and Mann–Whitney tests for non-homogeneous data, with a significance level of α = 0.05. The results showed greater improvements in the intervention group compared to the control group, particularly in knowledge (113.2% vs. 41.5%) and attitudes (66.6% vs. 9.9%). Positive caregiving practices increased in both groups by 13.3%. No significant differences were found between groups before the intervention; however, significant differences in knowledge, attitudes, and practices were observed after the intervention (p < 0.05). The Transfer of Knowledge and Skill model is recommended as an effective approach to improving nutrition-related caregiving practices and preventing stunting in early childhood.